Transcriptomic Analysis of Oenococcus oeni SD-2a Response to Acid Shock by RNA-Seq - Liu, Longxiang; Zhao, Hongyu; Peng, Shuai; Wang, Tao; Su, Jing; Liang, Yanying; Li, Hua; Wang, Hua (Frontiers in Microbiology, 2017)
The Oenococcus oeni is usually applied to conduct malolactic fermentation (MLF), and it is the preferred lactic acid bacteria (LAB) used in winemaking. Due to the high stress tolerance, it is an interesting model for investigating acid response mechanisms. In this study, the changes in the transcriptome of O.oeni SD-2a during the adaptation period have been studied. RNA-seq was introduced for the transcriptomic analysis of O. oeni samples treated with pH 4.8 and pH 3.0 at 0 h and 1 h, respectively. Gene ontology(GO) and Kyoto encyclopedia of genes and genome(KEGG) were performed to compare the transcriptome data between different treatments. From GO analysis, the majority of differentially expressed genes (DEGs) (pH3.0_1h-VS-pH4.8_1h, pH3.0_1h-VS-pH4.8_0h and pH4.8_1h-VS-pH4.8_0h) were found to be involved in the metabolic process, catalytic activity, cellular process and binding. KEGG analysis reveals that the most functional gene categories affected by acid are membrane transport, amino acid metabolism and carbohydrate metabolism. Some genes, like the heat shock protein Hsp20, malate transporter and malate permease, are also over-expressed in response to acid stress. In addition, a considerable proportion of gene indicate a significantly different expression in this study, are novel, which needs to be investigated further. These results provide a new viewpoint and crucial resource on the acid stress response in O. oeni.